The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4315/0362-028x.jfp-12-327
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Thermal Inactivation Kinetics of the Human Norovirus Surrogates, Murine Norovirus and Feline Calicivirus

Abstract: Studies are needed to bridge existing data gaps and determine appropriate parameters for thermal inactivation methods for human noroviruses. Cultivable surrogates, such as feline calicivirus (FCV-F9) and murine norovirus (MNV-1), have been used in the absence of human norovirus infectivity assays. This study aimed to characterize the thermal inactivation kinetics of MNV-1 and FCV-F9 at 50, 56, 60, 65, and 72°C for different treatment times (0 to 60 min). Thermal inactivation was performed using the capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 14 publications
3
49
3
Order By: Relevance
“…A major hindrance to human NoV research is the fact that the virus cannot be cultivated in cell culture and lacks a small-animal model. To date, much of the understanding of the molecular biology, pathogenesis, and environmental stability of human NoV has come from the study of other caliciviruses, which serve as human NoV surrogates (39)(40)(41)(42)(43). These surrogate viruses are cultivable in the laboratory and closely resemble human NoV with regard to size, genetic makeup, receptor binding, cell tropism, and disease manifestations.…”
mentioning
confidence: 99%
“…A major hindrance to human NoV research is the fact that the virus cannot be cultivated in cell culture and lacks a small-animal model. To date, much of the understanding of the molecular biology, pathogenesis, and environmental stability of human NoV has come from the study of other caliciviruses, which serve as human NoV surrogates (39)(40)(41)(42)(43). These surrogate viruses are cultivable in the laboratory and closely resemble human NoV with regard to size, genetic makeup, receptor binding, cell tropism, and disease manifestations.…”
mentioning
confidence: 99%
“…Thus, the choice of the most appropriate model is crucial to gather correct information about the thermal inactivation kinetic behavior of the target pathogen. Recent studies conducted on thermal inactivation of HNoV surrogates (21)(22)(23)(24)(25) and HAV (26,27) revealed that the Weibull model was statistically superior to the first-order model in describing the thermal inactivation kinetics of HNoV surrogates and HAV.…”
mentioning
confidence: 99%
“…With the discovery of murine norovirus (MNV) in 2003 (16), many researchers are now using this newly described virus, because it is genetically more closely related to human noroviruses and is resistant to low pHs (17,18). Many studies comparing FCV and MNV with or without other surrogates, such as MS2 coliphage and hepatitis A virus, as well as human norovirus (using reverse transcription-quantitative PCR [RT-qPCR]), have been published (4,(18)(19)(20)(21)(22)(23)(24). However, because MNV is highly sensitive to alcohols (18), the focus has expanded to cultivable calici-viruses such as TuV (14,(25)(26)(27)(28) and to porcine enteric calicivirus (PEC), a genogroup III (GIII) sapovirus (29,30).…”
mentioning
confidence: 99%